2008
DOI: 10.1103/physrevb.77.014102
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure structural behavior of large-void CoSn-type intermetallics: Experiments and first-principles calculations

Abstract: The high-pressure structural behavior of the binary intermetallic compounds CoSn, FeSn, and NiIn with the peculiar void containing CoSn ͑B35͒-type structure has been studied by means of room-temperature diamond anvil cell and high-temperature multianvil experiments, as well as by first-principles calculations. All three compounds remain structurally stable at pressures up to at least 25 GPa, whereas first-principles calculations predict high-pressure structural changes below 20 GPa. A plausible explanation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 61 publications
(36 reference statements)
3
23
0
Order By: Relevance
“…While this does not preclude the possibility of a distorted high-pressure phase that can relax back to the ambient form, the lack of decomposition products does prove that this material is stable with respect to the simple binaries under these conditions. CoSn reportedly decomposes upon heating to 1000°C at extreme pressures (26 GPa) [11] that we are unable to reach, so we cannot compare the relative stabilities of the two phases under those conditions Fig. 5 shows the temperature dependent magnetic susceptibility for x = 0, 1, and 2, that is for CoSn, Co 3 Sn 2 Ge, and Co 3 SnGe 2 .…”
Section: High Pressure Studiesmentioning
confidence: 93%
See 3 more Smart Citations
“…While this does not preclude the possibility of a distorted high-pressure phase that can relax back to the ambient form, the lack of decomposition products does prove that this material is stable with respect to the simple binaries under these conditions. CoSn reportedly decomposes upon heating to 1000°C at extreme pressures (26 GPa) [11] that we are unable to reach, so we cannot compare the relative stabilities of the two phases under those conditions Fig. 5 shows the temperature dependent magnetic susceptibility for x = 0, 1, and 2, that is for CoSn, Co 3 Sn 2 Ge, and Co 3 SnGe 2 .…”
Section: High Pressure Studiesmentioning
confidence: 93%
“…Calculations suggest that the structure should transform under high pressure to either the FeSi or CoGe structure types, and then finally to the cubic CsCl structure [11,12]. However, experimentally it is found that CoSn maintains its structure up to at least 38 GPa at ambient temperature, though heating under pressure causes it to dissociate into a combination of CoSn 2 and Co 3 Sn 2 [11,13]. It has been suggested that this unusual stability in spite of the small packing fraction arises from occupation of the void either by stereochemically active electrons from Sn [13] or a small amount of undetectable hydrogen [14].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These areas include the biological impact of electromagnetic emission, electromagnetic interference, energy conservation and emission as well as public health, especially prevention of hazards caused by electromagnetic emission systems [6]. Certain B20 often display interesting magnetic, thermal and transport properties despite the fact that the possibility of their corresponding phase transformation is problematic [7][8][9].…”
Section: Introductionmentioning
confidence: 99%